Differences in Neuropathology between Nitroglycerin-Induced Mouse Models of Episodic and Chronic Migraine - Park, Songyi; Jung, Harry; Han, Sang-Won; Lee, Sang-Hwa; Sohn, Jong-Hee (International journal of molecular sciences, 2024)
Multiple animal models of migraine have been used to develop new therapies. Understanding the transition from episodic (EM) to chronic migraine (CM) is crucial. We established models mimicking EM and CM pain and assessed neuropathological differences. EM and CM models were induced with single NTG or multiple injections over 9 days. Mechanical hypersensitivity was assessed. Immunofluorescence utilized c-Fos, NeuN, and Iba1. Proinflammatory and anti-inflammatory markers were analyzed. Neuropeptides (CGRP, VIP, PACAP, and substance P) were assessed. Mechanical thresholds were similar. Notable neuropathological distinctions were observed in Sp5C and ACC. ACC showed increased c-Fos and NeuN expression in CM (p < 0.001) and unchanged in EM. Sp5C had higher c-Fos and NeuN expression in EM (p < 0.001). Iba1 was upregulated in Sp5C of EM and ACC of CM (p < 0.001). Proinflammatory markers were strongly expressed in Sp5C of EM and ACC of CM. CGRP expression was elevated in both regions and was higher in CM. VIP exhibited higher levels in the Sp5C of EM and ACC of CM, whereas PACAP and substance P were expressed in the Sp5C in both models. Despite similar thresholds, distinctive neuropathological differences in Sp5C and ACC between EM and CM models suggest a role in the EM to CM transformation.